Correlation between clinical features of systemic lupus erythematosus and levels of antihistone antibodies of the IgG, IgA, and IgM isotypes. - Gompertz, N R (1990)
An attempt was made to define the correlation between the clinical features of systemic lupus erythematosus and levels of circulating antihistone antibodies of the IgG, IgA, and IgM isotypes. Serum antibody levels were determined by enzyme linked immunosorbent assay (ELISA) on serial blood samples (n = 4) from 25 patients, representing five subgroups: (a) renal disease; (b) central nervous system disorders; (c) skin and joint disease only; (d) serositis; and (e) deep venous thrombosis with or without spontaneous abortion. The levels of antihistone antibodies of each isotype varied widely from patient to patient, but antibody levels in the four samples from each patient correlated closely. A close correlation between levels of IgG and IgA antihistone antibodies was found but there was no correlation between these isotypes and IgM antihistone antibodies. In individual patients no simple correlation between disease activity and antihistone antibody levels was established, but levels of antihistone antibodies of the IgG and IgA isotypes were significantly higher in those patients in whom the disease was consistently more active.